1984
DOI: 10.1128/mcb.4.11.2347
|View full text |Cite
|
Sign up to set email alerts
|

Invertase beta-galactosidase hybrid proteins fail to be transported from the endoplasmic reticulum in Saccharomyces cerevisiae.

Abstract: The yeast SUC2 gene codes for the secreted enzyme invertase. A series of 16 different-sized gene fusions have been constructed between this yeast gene and the Escherichia coli lacZ gene, which codes for the cytoplasmic enzyme ,-galactosidase. Various amounts of SUC2 NH2-terminal coding sequence have been fused in frame to a constant COOH-terminal coding segment of the lacZ gene, resulting in the synthesis of hybrid invertase-,3-galactosidase proteins in Saccharomyces cerevisiae. The hybrid proteins exhibit j8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 44 publications
1
36
0
1
Order By: Relevance
“…The present data rule out the possibility that ADH III represents an altered form of ADH I or ADH II, perhaps arising from a different transcript as in the case of secreted invertase (6,12). The genes are unlinked (unpublished data), and the nucleotide sequences are different.…”
Section: Discussionmentioning
confidence: 80%
“…The present data rule out the possibility that ADH III represents an altered form of ADH I or ADH II, perhaps arising from a different transcript as in the case of secreted invertase (6,12). The genes are unlinked (unpublished data), and the nucleotide sequences are different.…”
Section: Discussionmentioning
confidence: 80%
“…The yeast strains used in this work were FLIOO (Mat a) [19], NC233-10B [MAT a, leu 2, [20] and SEY 5076 (MAT a, sec 7-1, uru 3-52, leu 2-3, leu 2-112) [21]. The last three strains were transformed with a multicopy plasmid pJDB 207 with (plasmid pAB4 [ l l ] ) or without the FCY2 insert, as previously described [ I l l .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous experiments have demonstrated that a signal sequence can direct cytoplasmic proteins to the secretory pathway in vivo (7,47,49). Based on these data, we reasoned that if a signal sequence were attached to a cytoplasmic enzyme required for the formation of an essential nutrient, the hybrid protein would be directed to the ER.…”
Section: A Selection Scheme For Yeast Translocation Mutantsmentioning
confidence: 99%